Remoção de alumínio em sistema contínuo por adsorção em coluna de leito fixo com carvão ativado - Oliveira, Letícia Raquel de (2014)
The pollution of the aquatic environment is a serious issue and central to debates worldwide, since water is a vital and extremely important also for industrial and economic development resource. Among the wide range of water pollutants are metals such as aluminum, though it is not categorized as a heavy metal significantly interfere in the aquatic ecosystem when in excess. The main source of aluminum in the water is due to residual found after treatment with aluminum salts such as aluminum sulfate. This growing concern for the environment has intensified the study of techniques for removal of metals from wastewater and raw water. In this sense, the adsorption has attracted attention because it presents itself as an effective, economical method, low cost and low energy consumption. Another point that draws attention is the fate of the solid adsorbent after use and saturation. In this sense, the activated carbon adsorbent stands out as the possibility of regeneration and reuse of this material in adsorption processes. Moreover, it presents a high surface area and its use as an adsorbent is consolidated decades. Thus, the objective of this study was to investigate the adsorption capacity of the activated carbon in the removal of residual aluminum effluent treated by the conventional coagulation/precipitation with aluminum sulfate, through the use of an adsorption column fixed bed after this type of treatment. Thus, adsorption experiments in fixed bed column were performed to investigate the influence of the feed flow ( 12.1 and 36.1 mL min-1 ), mass of adsorbent ( 6 and 12 g ) and size of coal ( 0.250 - 0.053 mm ) in the adsorption of residual aluminum in continuous system. For this, we determine the breakthrough curves of aluminum in synthetic wastewater containing approximately 5 ppm of aluminium at room temperature with a pH between 7.0 to 9.0. It was observed that at lower flow greater removal was achieved in addition, the particle size of the activated carbon showed no significant difference. The study showed that fixed bed with the increase of flow, the adsorption capacity of the bed increased and saturation time decreased. The results indicated that a lower flow rate and lower mass of adsorbent showed better removal efficiency. In the description of the breakthrough curves with the experimental data the model Thomas, Yoon & Nelson and Yan were reviews. The similarity between the models of Thomas and Yoon & Nelson Similar values of deviations, while the Yan model showed the best fit to the experimental data.